Applied Lean Warehousing-Based Optimization of Warehouse Processes at PT. XYZUsing Value Stream Mapping - Rahmawati, Nur; Rahmawati, Dea; Ramadhan, Rahandi Aliftyant (UNIPA PRESS, 2026)
Incoming warehouse operations are essential for maintaining material readiness in manufacturing systems. In practice, inefficiencies within these operations may increase lead time and generate activities that do not contribute to value creation. This study focuses on enhancing the performance of the incoming warehouse process at PT. XYZ through the application of lean warehousing supported by Value Stream Mapping (VSM). The study was carried out by examining the actual condition of receiving, recording, and storage activities using direct observation, time measurement, and process mapping. All identified activities were categorized according to their contribution to value creation. Process performance was assessed using Process Cycle Efficiency (PCE) to quantify the ratio of value-added time to total lead time. The results indicate that the existing incoming warehouse process required 296 minutes to complete, with a PCE of 74.66%, reflecting the presence of non-value-added activities, particularly related to waiting and unnecessary movement. Improvement actions were then formulated using future state value stream mapping and workplace organization. The proposed future condition reduced the total lead time to 273 minutes and increased the PCE to 80.95%. These findings show that lean warehousing implementation can effectively improve process efficiency by reducing non-value-added activities in incoming warehouse operations. The study provides practical insight for manufacturing companies seeking to improve inbound warehouse performance through structured waste reduction initiatives.